Enhancing the Creative Economy Potential Through the Empowerment of Visual Art Entrepreneurs: A Case Study of MSMEs in Bona Village, Blahbatuh District, Gianyar Regency - DEWI, I Gusti Ayu Agung Istri Sari; PURNAMAWATI, Ida Ayu Putu Santi; VIDYANTARI , Putu Kemala (PT Keberlanjutan Strategis Indonesia, 2025)
This community service activity was conducted under the Community-Based Empowerment (PBM) scheme, focusing on assisting creative visual art MSMEs (Micro, Small, and Medium Enterprises) of ARTPM BALI located in Bona Village, Blahbatuh Subdistrict, Gianyar Regency. These enterprises face several fundamental challenges, particularly in production management, marketing, and financial management. The program’s activities included providing production equipment (such as sewing machines, grinders, drill bits, and other supporting tools), training on the use of digital marketing technology through social media and e-commerce platforms, production management training, and the introduction of simple financial recording applications to support better cash flow management. The implementation of the program has shown positive outcomes. In the production sector, partners have improved work efficiency and product quality through the use of new equipment. In marketing, partners have become more active in promoting their products via social media and are exploring marketplace platforms as distribution channels. In financial management, partners have started to record daily transactions using digital applications, resulting in better cash flow control. Overall, this ongoing community service initiative has successfully enhanced the partners’ capacity to manage their businesses in a more modern and professional manner. Active participation of the partners in every stage of the program has been a key factor in its success. However, further stages are still required, particularly in providing continuous mentoring, strengthening branding, and conducting implementation monitoring to ensure long-term and sustainable impacts.